Evaluation of Protein Cards: A nutrition education tool for metabolic bariatric surgery - Patricia F. C. Acosta; Alexandra J. Heidl; Patricia M. Angeles; Biagina-Carla Farnesi; Peggy Alcindor; Angela S. Alberga; Julius Erdstein; Stephanie Saputra; Tamara R. Cohen (PLoS ONE, 2025)
Background Metabolic bariatric surgery (MBS) is a safe, effective treatment for severe obesity and its associated comorbidities. However, adherence to postoperative guidelines, particularly dietary protein intake remains a challenge. This study examined the suitability of the Protein Cards , a protein-focused nutrition education tool developed to support individuals meet their protein requirements during the postoperative diet stages: fluid, purée, soft, and regular. Methods An online adapted version of the Suitability Assessment of Materials questionnaire was administered from September 2020 to May 2021. Participants were recruited via convenience sampling and advertisement. Participants rated the rated as “superior”, “adequate” or “not suitable” on content, literacy demand, graphic illustrations, layout and typography, learning stimulation and motivation, and cultural appropriateness, with scores of 2, 1, and 0, respectively. Results A total of 437 individuals completed the online survey. Participants were identified as individuals who have undergone MBS (n = 263), caregivers of individuals who completed MBS (n = 68), and/or healthcare providers (including dietitians) specializing in MBS (n = 106). The Protein Cards received an overall “superior” rating of 73.00%. The tool had a high likelihood of use particularly for the soft diet stage (63.99 ± 20.70). Participants preferred the tool be available as a mobile application (63.41 ± 20.41) followed by paper book (59.40 ± 21.95) format. Conclusion Protein Cards have the potential of supporting individuals who have undergone MBS in adopting healthy dietary habits, particularly in meeting their protein requirements. Future studies are needed to refine the Protein Cards and evaluate its usability among individuals post-MBS.